Congregation Sites and Sleeping Roost of Male Stingless Bees (Hymenoptera: Apidae: Meliponini) - Charles Fernando dos Santos; Cristiano Menezes; Ayrton Vollet-Neto; Vera Lucia Imperatriz-Fonseca (Sociobiology)
Very little is known about stingless bee reproductive biology or male behaviour. In this note we provide the first observations on the male aggregations (congregation sites and roosting sites) of some stingless bee species. Our observations show that males of two stingless bee species can congregate on the same site. We also report for the first time the substrates used by stingless bee males for resting at night, that at least one species forms large sleeping roosts composed of hundreds of individuals, and that sleeping roost locations are not reused on subsequent nights.